Morphometric analysis in Google Earth Engine: An online interactive web-based application for global-scale analysis. (April 2023) - Şener, Mehmet; Arslanoğlu, Mehmet Cengiz
Abstract: Morphometric analysis of a basin or watershed describes the physical characteristics of the basin that are useful for environmental studies. Watershed morphometric characteristics are based on the terrain processing that must be done for each different watershed. There is no application that provides basin morphometric characteristics, basin borders, and streams in the basin on a global scale, so the development of a new application has become a necessity. In this research, an online Google Earth Engine (GEE) application has been developed that determines the morphometric characteristics of any watershed on a global scale using digital elevation models, basin boundaries, and river stream data. The Meriç basin was selected for testing the application. The results of the application were validated by comparing them to ArcGIS. The findings demonstrate that, in the absence of GIS software or data, GEE may be used to determine basin morphometric characteristics on a worldwide scale. Highlights: Global scale morphometric characteristics of any watersheds. No need GIS, DEM for obtaining morphometric characteristics. Online monitoring and downloading of basins and watershed borders with streams. Stream order classification using Strahler's ordering system. Find upstream or downstream of any stream segment.